A Study to Assess the Effectiveness of Structured Teaching Programme on Knowledge & Practice of Basic Life Support in Emergency Department Nurses in Selected Hospitals, Bangalore - Shashi Kumara H S; Jelish Sharma Phurailatpam; Geetanjali Devi; I Clement, (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2021)
The human heart is a muscular organ that provides a continuous blood circulation through the cardiac cycle and is one of the most vital organs in the human body. The term cardiac arrest implies the sudden interruption of cardiac output, which may be reversible with appropriate treatment most reliable sign of cardiac arrest is the absence of pulse. For patients with cardiac arrest ,survival rates and neurologic outcomes are very rare, through early detection and appropriate resuscitation ,involving cardiopulmonary resuscitation appropriate implementation of cardiac arrest can leads to survival and neurologic outcomes A combination of rescue breathing and chest compression is known as cardiopulmonary resuscitation (CPR) which forms the basis of modern basic life support [1]. Cardiopulmonary resuscitation (CPR) is an emergency procedure for people in cardiac arrest or, in some circumstances, respiratory arrest. CPR is performed both in hospitals and in pre-hospital settings. CPR may be necessary during many different emergencies, including accidents, near-drowning, suffocation, poisoning, smoke inhalation, electrocution injuries, and suspected sudden infant death syndrome (SIDS). Importance of Cardiac Resuscitation of sudden cardiac arrest is a leading cause of death, approximately 250,000 per annum outside a hospital setting in the U.S.A. The American heart Association and American Red Cross offers courses in basic first aid. In 2016 the absolute prevalence of CVD in India is 54.6 million in over 60 percent larger than in the US 33.6 million.